ANALISIS KOMPETENSI DIGITAL GURU DALAM MENINGKATKAN KINERJA DI SEKOLAH MENENGAH PERTAMA NEGERI 3 PALOPO - Sari, Resky; Taqwa, Taqwa; Salmilah, Salmilah (ASCENT: Al-Bahjah Journal of Islamic Education Management, 2025)
This study explores teachers’ digital competence in improving performance at SMP Negeri 3 Palopo. The objective of this research is to examine teachers’ digital competence and work performance, as well as the opportunities and challenges in enhancing such competence. The study employs a qualitative approach using descriptive phenomenology. Data collection techniques include interviews, observation, and documentation study. The research subjects are the school principal, teachers, and students. Data were analyzed through an interactive model comprising data condensation, data display, and conclusion drawing. The findings reveal that teachers’ digital competence is considered fairly good, as many teachers have begun to integrate digital systems into the learning process; Teacher performance has improved due to continuous efforts in developing digital skills through training programs and internal collaboration; and The main challenge is the limited digital skills among some teachers. Nevertheless, the use of digital systems presents great opportunities to create a more conducive working environment and enable teachers to apply various innovative teaching methods. The study concludes that teachers’ digital competence plays a significant role in enhancing work performance in school settings.